2011
DOI: 10.1136/archdischild-2011-300612
|View full text |Cite
|
Sign up to set email alerts
|

Correction

Abstract: background NICU safety culture, as measured by the Safety Attitudes Questionnaire (SAQ), varies widely. Associations with clinical outcomes in the adult ICU setting make the SAQ an attractive tool for comparing clinical performance between hospitals. Little information is available on the use of the SAQ for this purpose in the NICU setting. objectives To determine whether the dimensions of safety culture measured by the SAQ give consistent results when used as a NICU performance measure. methods Cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 29 publications
6
50
0
2
Order By: Relevance
“…The predominance of females in the profession of nursing is justified by the historical trajectory of the profession and confirms other studies (15)(16)(17)(18) . We highlight that the working time in the institution and the experience in the unit resembled international studies (17,(19)(20) and a national study (15) , in which they evaluated the safety climate in both clinical and intensive care units, but we noted that the values were lower than those of other studies (16,18) .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The predominance of females in the profession of nursing is justified by the historical trajectory of the profession and confirms other studies (15)(16)(17)(18) . We highlight that the working time in the institution and the experience in the unit resembled international studies (17,(19)(20) and a national study (15) , in which they evaluated the safety climate in both clinical and intensive care units, but we noted that the values were lower than those of other studies (16,18) .…”
Section: Discussionsupporting
confidence: 70%
“…Among the factors, two are related to the reliability and management commitment to safety, which should stimulate the commitment of the professionals with security issues, setting and reinforcing standards and safe practices, generating a positive perception of patient safety culture (22) . The low-scoring identified in this study for the domain stress recognition has also been reported by other authors in the literature (13,16,(19)(20)(21) . Still with prominence for this domain, study conducted to evaluate the internal validity of this construct pointed out that this construct do not fit the assessment of global safety climate of the SAQ, justifying that this domain evaluates the perception of the professional regarding skills, unlike other domains, that evaluate the perception of the professional regarding the workplace or the organizational unit as a whole (12) .…”
Section: Discussionsupporting
confidence: 59%
“…Various organizational research articles have provided the basis for the theoretical framework used to develop the study hypotheses [8][9][10][11][12][13][14][15] . The exogenous variables in this study are Effective Communication (EC), Safety Culture (SC), Job Satisfaction (JS), Work Pressure (PR), and Work Climate (WC).…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…However, based on these results, and since our study was only conducted in pediatric settings, we believe that the professionals' perceptions of the pediatric patient safety grade is higher. In the same line, when comparing studies conducted in neonatal intensive care units and adult intensive care units, Profit et al (2012) concluded that the scores on safety culture were higher in neonatal units. By analyzing the specific patient safety grade assigned by the professionals to their service, we found that most respondents (68.9% in H1 and 58.2% in H2) considered it to be very good.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to our study, several Portuguese researchers obtained less than 50% of positive answers, namely Sousa (2013) with 24%, Gomes (2012) with 28%, DGS (Direcção-Geral da SaĂșde, Departamento da Qualidade na SaĂșde, 2011) with 48% and Fernandes and QueirĂłs (2011) with 44%. In a study carried out exclusively in neonatal intensive care units, Profit et al (2012) also found perceptions of lack of support from hospital management. These results suggest the need for hospital management to reveal the activities being in fact developed for the promotion of the safety and quality of care provision.…”
Section: Discussionmentioning
confidence: 99%